DISIPLIN ANAK DALAM KEGIATAN BELAJAR DI MADRASAH DINIYAH AWALIYAH (MDA) DARUL AMAL DI KELURAHAN TUAH MADANI KECAMATAN TAMPAN KOTA PEKANBARU - Yurnalisa Sari; Jasfar Jas; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it is based on on with discipline a child in the study in Madrasah Diniyah Awaliyah (MDA) Darul Amal di Kelurahan Tuah Madani Kecamatan Tampan Kota Pekanbaru. Because discipline is an attitude willingness and mutual consent someone to adhere and obey norms regulations around. The formulation of a problem of this research is how high in jakarta the success of discipline a child study in Madrasah Diniyah Awaliyah (MDA) Darul Amal di Kelurahan Tuah Madani Kecamatan Tampan Kota Pekanbaru?. The purpose of this research is to know discipline a child in participated in the ppa are continuing their studies in Madrasah Diniyah Awaliyah (MDA) Darul Amal di Kelurahan Tuah Madani Kecamatan Tampan Kota Pekanbaru. Population in this study as many as 50 people learn. Then the researcher determine samples from 55 people for research in Madrasah Diniyah Awaliyah (MDA) Darul Amal di Kelurahan Tuah Madani Kecamatan Tampan Kota Pekanbaru and 20 people to of the tryouts in MDA Alwahidin with using a technique sampling jenuh. Invest in e instruments of data collection other of any economic indicators muamalat ran into financial difficulties with 55 a statement and if the trial live 51 statement mainly devoted to attacking valid for in could have made some of the research done by the instrument. The data analysis support for new through a descriptive analysis quantitative. The outcome of the findings the research indicated that discipline a child in their activities to get are continuing their studies in Madrasah Diniyah Awaliyah (MDA) Darul Amal di Kelurahan Tuah Madani Kecamatan Tampan Kota Pekanbaru most were high unflinching in do their tasks, with a percentage (SS+S) 80 %. It means child has discipline in do their tasks independently.Key words: Discipline, Discipline a child in the study in MDA